Map of Vienna - Gavard, Charles, 1794- (engraver):::Creator::::::::::::; Dufour, A.-H. (Auguste-Henri), 1798-1865 (cartographer); Bénard (engraver):::Contributor:::::::::::: (Paris; France; Publié par Jules Renquard Libraire)
Map of Vienna, including key of districts, attractions, and monuments in French.